The view from Alameda Island [large type] - Carr, Robyn (Thorndike Press Large Print basic, 2019)
"From the outside looking in, Lauren Delaney has a life to envy--a successful career, a solid marriage to a prominent surgeon and two beautiful daughters who are off to good colleges. But on her twenty-fourth wedding anniversary Lauren makes a decision that will change everything. Facing an uncertain future, Lauren discovers an inner strength she didn't know she had as she fights for the love and happiness she deserves."--